Posterior Reversible Encephalopathy Syndrome (Pres) - A Case Report - Melis Türker; Pınar Zeyneloğlu; Arash Pirat; Coşkun Araz; Fuldem Dönmez; Ufuk Can; Zeynep Kayhan (Galenos Yayinevi, 2011)
Posterior reversible encephalopathy syndrome (PRES) is a transient cliniconeuroradiological condition characterized by headache, visual disturbances, seizures and altered mental status. These clinical manifestations are most commonly associated with arterial hypertension, preeclampsia/eclampsia and immunosuppressive agents. Magnetic resonance imaging (MRI) studies typically show edema in the white matter of cerebral posterior regions. A case of an elderly woman with a history of hypertension who demonstrated PRES after a recent cancer surgery is presented. (Journal of the Turkish Society Intensive Care 2011; 9: 103-6)